PENGARUH SUSTAINABILITY REPORTING DAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Energi yang Terdaftar di Bursa Efek Indonesia Periode 2021–2023) - Akbar Adelio Hasiholan; Imam Ghozali (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of sustainability reporting and corporate governance on firm value. The independent variable in this study is sustainability reporting which is assessed based on the GRI 2021 index, while corporate governance is proxied by board size, board independence, and board diversity. Firm value, which is the dependent variable, is measured using the Tobin's Q indicator. The population in this study are energy companies listed on the Indonesia Stock Exchange (IDX) during 2021-2023. Using purposive sampling method, 76 samples were selected from energy sector companies that published sustainability reports with GRI Standards. This study used multiple linear regression analysis method to examine the effect of sustainability reporting, board size, board independence, and board diversity on firm value. The results showed that board size has a positive and significant effect on firm value, while sustainability reporting, board independence, and board diversity have an insignificant effect on firm value.